Diplomatica on-line: recensione del sito Thélème. Techniques pour l'Historien en Ligne: Études, Manuels, Exercices (École Nationale des Chartes), http://theleme.enc.sorbonne.fr/ - Guglielmotti, Paola (Scrineum, 2013)
The site has been conceived by authoritative members of the Parisian École des Chartes and makes the most of some its resources, mostly the iconographic ones, being a very effective didactic tool especially as regards a hundred cards with reproduction, translation and diplomatics-historical comment of documents of the whole Middle Ages and some well structured bibliographies.